ANALYSIS OF THE LAND MARKET IN UKRAINE: RETROSPECTIVE AND CURRENT STATE - KOSTENIUK, Yuliia; SHYROKA, Daryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The scientific article analyzes the processes of formation and functioning of the agricultural land market in Ukraine. In particular, it highlights the historical aspects of land policy from the time of the Land Decree of 1917 to the lifting of the moratorium on the sale of agricultural land in 2021. The study includes a number of measures introduced to establish a favorable situation on the land market in Ukraine in the period from the declaration of independence in 1991 to the present. Particular attention is paid to the analysis of the functioning of the market after its opening, the dynamics of transactions, the weighted average cost of 1 hectare of land, sales volumes and new challenges that have arisen against the background of reforms.  The article also describes the difficulties that Ukrainian citizens faced after the Russian invasion of the land market, namely: a decrease in the number of transactions, loss of land area, a decrease in the activity of notaries, as well as economic losses in the agricultural sector. The study highlights problems related to regulatory barriers, a new system for assessing the value of shares, and difficulties with the logistics of crop sales, which significantly affect farmers' decisions about purchasing land. The consequences of the second stage of land reform, which started in 2024, are considered, in particular, the opening of the market to legal entities.  As a result, the key factors influencing the land market today are outlined, and promising areas of development are proposed, namely: digitalization of the cadastral system, stimulation of transaction transparency, improvement of state regulation mechanisms and support for small agribusiness. The research is relevant for specialists in economics, law, and public administration, as well as for land market participants.
Keywords: land market; moratorium on land sales; agricultural land turnover; land reform